On the eve of capturing Halych by Mstislav Mstislavich (late March – early April 1221): a prosopography of the participants in the battle - Voloshchuk, Myroslav (Before the Battle, 2023)
The article presents the analysis of the list of the participants in the battle for Halych between the end of March and early April 1221. The main sides of the conflict were the King of Halych and the Hungarian Prince Coloman with his allies and the representative of the Smolensk branch of the Mstislavovids Prince of Torchesk Mstislav Mstislavich and his supporters. The scope of information provided in written records allows us to classify the aforementioned battle as one of the largest not only in Galicia (and more specifically for its capital) but in general – in the lands of the Rurikids until the Mongol invasion. This is confirmed not only by the results of the prosopographic studies carried out in this publication but also by unique for the Rus’-Hungarian inter-dynasty relationships – the first and only one instance when the Hungarian-Polish royal couple (King Coloman and his wife Salomea) by a Rus’ prince, their long imprisonment and further diplomatic negotiations on the conditions of their release. The brilliant victory of Prince Mstislav was determined both by the scale of resources mobilized for the campaign from the Kyiv, Smolensk and, the Cuman steppe and the unyielding attitude of Halych’s defenders. For over a year Coloman and his companions-in-arms fortified and actively defended the city. The fatality of the besieged King of Galicia’s position on the eve of the capturing of Halych by the Rus’ Princes was worsened by the absence of his father Andrew II in Hungary, who together with his wife, the eldest son Béla and daughter Maria, as part of the large delegation, travelled to the Bulgarian border at the beginning of March 1221 (a fact that Prince Mstislav was aware of), which prevented the Arpads to quickly come to the Coloman’s rescue.